Search for supersymmetry with jets, missing transverse momentum and at least one hadronically decaying τ lepton in proton–proton collisions at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
A search for production of supersymmetric particles in final states containing jets, missing transverse momentum, and at least one hadronically decaying τ lepton is presented. The data were recorded by the ATLAS experiment in √s = 7 TeV proton–proton collisions at the Large Hadron Collider. No excess above the Standard Model background expectation was observed in 2.05 fb−1 of data. The results are interpreted in the context of gauge mediated supersymmetry breaking models with Mmess = 250 TeV, N5 = 3, μ > 0, and Cgrav = 1. The production of supersymmetric particles is excluded at 95% C.L. up to a supersymmetry breaking scale Λ = 30 TeV, independent of tan β, and up to Λ = 43 TeV for large tan β.